Toxicity Profile of Commonly Used Anti-Inflammatory Drugs in Geriatrics - Alhouzani, Talal M. Ziad (Europasian Journal of Medical Sciences, 2020)
Background: Anti-inflammatory drugs are commonly used in geriatrics. Geriatrics usually encounter problems of pain and inflammation and are more vulnerable to the toxicity of drugs as compared to young patients. In this review, we aimed to find out the toxic profile of drugs and the pharmacotherapy considerations for geriatric care. Methods: The electronic databases like Google Scholar, PubMed, ScienceDirect, and different related text books of recent edition were searched using specific keywords for preparing this narrative review. Related experts in the field were also consulted. Papers published in English language were included in the review. Results: The diseases geriatrics mostly suffered from are osteoarthritis (OA), ankylosing spondylitis, carcinoma, and other degenerative disorders that require anti-inflammatory medicines. Non-steroidal anti-inflammatory drugs (NSAIDs) and corticosteroids are mostly used agents for the treatment of inflammation in such population. As the pharmacokinetics of drugs get altered due to alteration in body physiology in geriatrics, the pharmacodynamics also gets affected, and hence toxicity ensues even with normal dose. Depending upon the nature of the drugs, presence of comorbidity, and poly-pharmacy; gastrointestinal, renal, and cardiovascular toxicities occur. Due to this reason, utmost care should be taken for pharmacotherapy practice in geriatrics. Conclusion: In geriatrics, the anti-inflammatory drugs should be used rationally for the shortest duration possible at the lowest effective dose. The careful evaluation of the beneficial and potential risks of the agents and pharmacovigilance must be considered for pharmacotherapy practice in such populations.